Report on the scoping study for the project “nature positive solutions for shifting agrifood systems to more resilient and sustainable pathways" - Manibhai, Desai Nagar (2024)
The concept of Nature Positive production systems has emerged from the dire need to overcome the impacts of industrial agriculture on our food production system. The overexploitation and degradation of finite resources has necessitated the importance of designing an agri-food system that is not detrimental to the planet’s health. Nature Positive agriculture is regenerative, nondepleting and non-destructive use of natural resources to cover the growing demand for food sufficiently and include sustainable and healthy nutrition. NPS is designed through 5 major pillars which envision the creation of a sustainable food production system that can support food security and livelihood opportunities, namely Conserve, Manage, Restore, Recycle, and Engage. This Scoping Study was conducted in the Akole cluster of Maharashtra, India. Secondary research was conducted and the findings were triangulated with primary studies. As a next step, existing Nature Negative Practices were documented and analyzed so that appropriate nature positive interventions could be suggested. In addition, best nature positive practices currently in practice have been recorded for upscaling and possible replication. The aim of Nature Positive approach is not only to introduce interventions at the grassroots level, but also to shape the discourse and policy dialogue. Once the true cost of production is factored in, it can aid in scientifically calculating the environmental impact of food production systems in monetary terms. This will influence governing systems at local, national and global levels to design policies that favour a paradigm shift in agriculture to a more nature-positive approach. Economic policies and incentives thus framed keeping in mind the objective of Nature Positive Solutions can automatically improve the agri-food production system